Some Investigations About al-Sarakhsi’s Prisoned Life - Tashtanova, Ayzada (Scientific Journal of Faculty of Theology, 2022)
Al-Sarakhsi was imprisoned in 1073 (466 hijri) and in 1087 (480 hijri) he was emancipated. During his 14 years in prison, there were 3 khans on the throne: Shamsulmulk II Nasr ibn İbrahim (1068-1079), Abu Shuja Khizir Khan (1079-1080) and Ahmad Khan (1081-1088). These three khans had conflicts with the fuqaha from time to time, even some of them had executed. And it is possible to guess that İmam al-Sarakhsi was one of these faqihs. In the Tabakat works, there are some news about the reason for the imprisonment of İmam al-Sarakhsi, that he was imprisoned because of “a word containing advise” to the ruler of the time. Al-Sarakhsi had mentioned his prison life, the difficulties of those days and the reason that brought him to prison in a total of 23 passages, including 19 passages of al-Mabsut, 1 passage of Usul al-Fiqh and 1 passage of Sharh al-Siyar al-Kabir.